Alpha cut for interactive image segmentation of thin and elongated objects. Issue 11 (7th August 2019) - Tran, Nam H.; Seo, Dongsun; Woo, Dongmin; Won, Yongyuk; Tu, Hieu T.
Abstract : Shrinking bias problem is a practical limitation of graph‐cut‐based methods for binary image segmentation. The detail parts with thin elongated object are not well preserved in graph cut minimisation as a result. The authors propose to use structure transferring to overcome the problem with an expanded L2 norm of colour difference. They also show that the structure‐transferring output can be integrated into graph cuts as a counter‐balance to shrinking problem. Experimental results show that the proposed alpha‐cutting technique is effective and efficient in improving segmentation of thin elongated objects.